Makna Tanda dalam Struktur Fragmen Tari Topeng Sekartaji Karya S. Ngaliman: Kajian Semiotika Fredinand de Soussure - Indah Cahyasari; Paimin Paimin (Universitas Negeri Medan, 2026)
This study aims to analyze the meaning of sign structures in the dance fragment Topeng Sekartaji by S. Ngaliman using Ferdinand de Saussure’s semiotic approach. This research is motivated by the limited interpretative readings of dance works. Although Topeng Sekartaji is frequently performed in various events, the understanding of its structural meaning has not been widely explored; thus, the symbolic meanings constructed through elements such as movement, mask, character, music, and costume are not yet fully interpreted. The focus of this study lies in examining the relationship between the signifier and the signified as manifested through choreographic elements. This study employs a qualitative case study method with a non-participatory observation technique using documentation from the UPT Audio Visual ISI Surakarta YouTube channel, recorded during a performance on January 17, 2019, in the event “Mengenang Gendhon Humardani & Agus Tasman. ”The findings reveal that the Topeng Sekartaji dance fragment serves as a symbolic representation of the emotional relationship between Sekartaji, Panji, and Klana. Panji signifies wisdom, patience, and gentleness, whereas Klana represents anger, ambition, and aggression. Sekartaji symbolizes the ideal Javanese woman, characterized by grace, patience, and devotion. The denotative meaning of this dance reflects a love triangle narrative, while its connotative meaning embodies Javanese philosophical values concerning loyalty, honor, and the duality of good and evil.